Massage Therapy Can Prevent the Risk of Autism Spectrum Disorders in Children Aged 18-36 Months - Andy Martahan Andreas; Ratna Djuwita; Helda Helda; Rini Sekartini; Sri Hartati R. Suradijono; Thjin Wiguna; Angela B. M. Tulaar; Jusuf Kristianto (Humanistic Network for Science and Technology (HNST), 2021)
Background: Research on massage therapy for children with autism spectrum disorders conducted over a period of 10-15 years is mostly aimed at children who have been diagnosed with autism spectrum disorders with the average age of children being between 3-6 years. Meanwhile, research on massage therapy in children at risk for autism spectrum disorders, especially in Indonesia, has not been widely published. Aims: This study aims to provide an overview of the results of massage therapy in an effort to prevent the risk of autism spectrum disorders in children aged 18-36 months. Methods: The study was conducted from May 2019 to March 2020 at three community health centers in Jakarta, 10 children aged 18-36 months who were previously screened with M-Chat were then given massage therapy for 40 times to see the effect on changes in status risk of autism spectrum disorderThe results of therapy were then assessed by modifying the M-Chat score through the receiver operating characteristic (ROC) in order to obtain a new cut off point to determine the risk status of autism spectrum disorders. Results: The results of massage therapy showed that there was a decrease in M-Chat scores and changes in the risk status of autism spectrum disorders starting in the third period of 30 days of massage therapy. Conclusion: The conclusion of this study is that massage therapy can change the risk status of ASD children from autism risk to normal to prevent the risk of autism spectrum disorders.Keywords: massage therapy; autism spectrum disorder risk; modified check list for autism in toddler